2007
DOI: 10.1021/ct700224j
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Standard 6-31G and Binning-Curtiss Basis Sets for Third Row Elements

Abstract: Ab initio calculations were carried out for isogyric reactions involving the third row elements, Ga, Ge, As, Se, and Br. Geometries of all the reactants and products were optimized at the HF, MP2, and B3LYP levels of theory using the 6-31G(d) and 6-31G(d,p) basis sets. For molecules containing third row elements geometries, frequencies and thermodynamic properties were calculated using both the standard 6-31G and the Binning-Curtiss (BC6-31G) basis sets. In order to determine the performance of these basis set… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 43 publications
0
15
0
Order By: Relevance
“…The theoretical value of the C-C bond length in CCAs, r C-C = 1.2933 Å, calculated with density functional methods at the B3LYP/aug-cc-pVTZ level, 18 is in reasonable agreement, as well as r C-As = 1.7341 Å, determined from the laser-induced fluorescence ͑LIF͒ experiments of Wei et al 18 Table V also summarizes the C-As and C-C bond lengths of other relevant molecules. 15,17,18,20,[25][26][27][28][29] The ethylene C-C bond length of 1.339 Å is representative for a C v C double bond, while the acetylene C-C bond length, 1.202 Å, is typical of a C w C triple bond. Our experimental C-C bond distance of 1.287 Å for CCAs falls almost midway between the double and triple bond values.…”
Section: Discussionmentioning
confidence: 99%
“…The theoretical value of the C-C bond length in CCAs, r C-C = 1.2933 Å, calculated with density functional methods at the B3LYP/aug-cc-pVTZ level, 18 is in reasonable agreement, as well as r C-As = 1.7341 Å, determined from the laser-induced fluorescence ͑LIF͒ experiments of Wei et al 18 Table V also summarizes the C-As and C-C bond lengths of other relevant molecules. 15,17,18,20,[25][26][27][28][29] The ethylene C-C bond length of 1.339 Å is representative for a C v C double bond, while the acetylene C-C bond length, 1.202 Å, is typical of a C w C triple bond. Our experimental C-C bond distance of 1.287 Å for CCAs falls almost midway between the double and triple bond values.…”
Section: Discussionmentioning
confidence: 99%
“…All calculations were conducted with the Gaussian 09 software package [19]. From previous work [20,21], it was found that geometries, solvation free energies, dipole moment and molecular properties of similar systems obtained using the B3LYP/6-31G(d,p) showed better agreement with experiments. Therefore, methylimidazole geometries were optimized at the B3LYP electronic structure method [22][23][24] using the 6-31G(d,p) basis set.…”
Section: Methodsmentioning
confidence: 99%
“…Calculations of the title compound were carried out with the Gaussian 03W program [7] using B3LYP/6-31G(d,p) basis set to predict the molecular structure and vibrational wave numbers and a scaling factor of 0.9608 is used for obtaining a considerably better agreement with experimental data [8,9]. The assignments of the calculated wave numbers are aided by the animation option of the VEDA4 [10] program.…”
Section: Computational Detailsmentioning
confidence: 99%